Amygdala reactivity and connectivity during social and non-social aversive stimulation in social anxiety disorder. (30th October 2018) - Kraus, Jakub; Frick, Andreas; Fischer, Håkan; Howner, Katarina; Fredrikson, Mats; Furmark, Tomas
Highlights: SAD is associated with increased amygdala reactivity to socially relevant cues. Social anxiety severity was positively related to amygdala reactivity. SAD patients had attenuated amygdala reactivity to generally aversive cues. Amygdala-prefrontal connectivity did not differ between patients and controls. Abstract: Social anxiety disorder (SAD) is characterized by exaggerated amygdala reactivity in response to symptom provocation, but it is unclear if such hyper-reactivity is elicited by disorder-specific challenges only or characterizes reactions to aversive stimuli in general. Here, using functional magnetic resonance imaging in 14 patients with SAD, as compared to 12 healthy controls, we found that amygdala hyper-reactivity is confined to disorder-relevant social stimulation. SAD patients displayed increased amygdala reactivity to fearful as compared to neutral facial pictures, but not in response to generally aversive but mainly non-social stimulation when compared to neutral pictorial stimuli taken from the International Affective Picture System. The increased amygdala reactivity was not mediated by an altered prefrontal inhibition among SAD patients as compared to controls, suggesting increased bottom-up processes rather than attenuated top-down control. In conclusion, the enhanced amygdala reactivity in SAD seems specific to socially relevant stimuli rather than aversive stimuli in general.